National characteristics associated with prevalence of depression and anxiety symptoms: a cross-sectional ecological study - Anthony F. Jorm; Roger T. Mulder (Cambridge Prisms: Global Mental Health, 2022)
Abstract Background Cross-national comparisons of the prevalence of mental disorders have relied on lay-administered interviews scored using complex diagnostic algorithms. However, this approach has led to some paradoxical findings, with more vulnerable countries showing lower prevalence, and its appropriateness for cross-national comparisons has been questioned. This study used an alternative method involving simple questions from social surveys to assess the prevalence of specific depression and anxiety symptoms, and investigated their association with national indicators of human development, quality of government, mental health resources, and mental health governance.